A Phenomenological Study of Educators’ Experiences with Neurodiverse Students in Public Elementary Schools - Reyes, Renebeth; Sabud, Marilou; Fuentes, Augie; Almerez, Queenie Lyn; Arnado, Jeric Anthony (Journal of Interdisciplinary Perspectives, 2025)
This study aims to explore the lived experiences, teaching strategies, support needs, and insights of teachers handling neurodiverse learners (NLs) in public elementary schools. Using a descriptive-phenomenological qualitative approach, data were gathered through in-depth interviews with 30 teachers in Digos City Division and analyzed thematically. Findings reveal that personal growth, emotional challenges, evolving roles, and collaboration shaped their teaching journeys. Teachers implemented a variety of strategies, including adaptive techniques, inclusive practices, and classroom management approaches that foster safe and supportive learning environments. These strategies often stemmed from a combination of formal training, peer support, and practical experience. A central theme in support needs was the call for stronger institutional and professional structures. Teachers also shared meaningful reflections, highlighting dedication, the importance of continuous learning, appreciation for diversity, and a focus on whole-child development. While educators show resilience and commitment, the study underscores the need for enhanced systemic support, including targeted professional development, collaborative opportunities, and inclusive school policies. Understanding teacher perspectives provides valuable guidance for creating effective and inclusive environments that benefit both neurodiverse learners and their educators.